2016
DOI: 10.1111/apt.13726
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: low‐FODMAP rye bread vs. regular rye bread to relieve the symptoms of irritable bowel syndrome

Abstract: SummaryBackgroundGrains are high in FODMAPs (Fermentable Oligo‐, Di‐, Monosaccharides And Polyols) and often considered as triggers of IBS symptoms.AimTo evaluate if rye bread low in FODMAPs would be better tolerated than regular rye bread in subjects with IBS.MethodsThe study was conducted as a randomised double blind controlled cross‐over study (n = 87). Participants were supplied with both regular rye bread and low‐FODMAP rye bread for 4 weeks. Symptoms were measured with a symptom severity scoring system (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 27 publications
2
96
0
1
Order By: Relevance
“…Hydrogen and methane breath tests consider as a marker of colonic fermentation. So breath hydrogen/methane production is lower during low FODMAP diet …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hydrogen and methane breath tests consider as a marker of colonic fermentation. So breath hydrogen/methane production is lower during low FODMAP diet …”
Section: Discussionmentioning
confidence: 97%
“…But it has been proven that these recommendations are often ineffective for IBS sufferers. In fact, current standard dietary advices are not based on evidence from controlled clinical trials and offer general dietary advices (GDA) for the management of disease . A new approach suggests that intake of fermentable oligo‐di‐mono‐saccharides and polyols (FODMAPs) can aggravate the GI symptoms of IBS.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 reports the clinical trials that are available in the literature on the effect of a low-FODMAP diet in IBS patients [3,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. In general, most studies and one meta-analysis [6] have shown that IBS symptoms, particularly bloating and abdominal pain, may benefit from this treatment.…”
Section: Efficacy Of the Low-fodmap Diet: What Is The Quality Of Tmentioning
confidence: 99%
“…Among the nonpharmacological measures, it is possibly highlighting the actions taken to reduce stress (a factor strongly associated with crises) and food adequacy through the restriction of certain food (i.e., FODMAPs) associated with the onset of symptoms [10][11][12][13]. The distension caused by unabsorbed and/or fermented FODMAPs can be the basis for the most common symptoms in IBS [1,14]. Table 1 [15] presents the main sources and maximum intake dose of FODMAPs not associated with the onset of symptoms in individuals with IBS.…”
Section: Fodmaps and The Irritable Bowel Syndromementioning
confidence: 99%